Experimental Study of the Dissection Properties of Porcine Aorta - Ríos Ruiz, Itziar; Martínez Barca, Miguel Ángel; Peña, Estefanía (Jornada de Jóvenes Investigadores del I3A, 2020)
Aortic dissection can be a fatal disease and its biomechanics is still unclear. A full study of the dissection of healthy porcine aortas was carried out via two different experimental tests. The study includes the dissection of all layers through different locations of the aorta.